Léri-Weill syndrome as part of a contiguous gene syndrome at Xp22.3 - Spranger, Stephanie; Wöginger, Simone; Jauch, Anna; Wolff, Kathrin; Rauterberg-Ruland, Inge; Hager, Dieter; Tariverdian, Gholamali; Tröger, Jochen; Rappold, Gudrun (American journal of medical genetics, 1999)
We report on a mother and her 5-year old son, both with a terminal deletion of the short arm of the X chromosome. By molecular genetic analysis the breakpoint was located distal to steroid sulfatase gene. The boy manifested, due to nullisomy of this region, short stature (SHOX), chondrodysplasia punctata (ARSE), and mental retardation (putative mental retardation gene MRX 49). Short stature is present in mother and son, but both also had bilateral Madelung deformity, a key finding in the Léri-Weill syndrome.We discuss the phenotype in relationship to hitherto published cases with chromosomal aberrations and contiguous gene syndromes of Xp22.3. Am. J. Med. Genet. 83:367-371, 1999. © 1999 Wiley-Liss, Inc.
Gesehen am 04.12.2020